2021
DOI: 10.1021/acs.jpclett.1c02173
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Atmosphere Effect on the Absorption Spectrum of a Flavoprotein: A Reminder to Consider Solution Ions

Abstract: Ionizable residues and monoatomic ions in solution modulate enzyme catalysis and the structural stability of proteins; however, the delicate interplay between these short-range charges and longrange charges, and their contributions to the electrostatic environment in a protein active site, is currently not fully understood. The study presented here utilizes the FMN-dependent NADH:quinone oxidoreductase from Pseudomonas aeruginosa PAO1 (NQO, EC 1.6.5.9, UniProtKB Q9I4V0) as a model system to study the effect of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 80 publications
0
27
0
Order By: Relevance
“…In a recent joint computational and experimental study, (56) we found that solution ions may affect the outcome of ASEC-FEG calculations, especially when there are charged residues inside the active site of a flavoprotein. Therefore, we repeated the calculations for both iLOV and iLOV-Q430E after adding 4 pairs of Na+ and Cl-solution ions, approximately 1 NaCl per 2775 water solvent molecules, equivalent to 20 mM of salt used in the experiments in this work.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…In a recent joint computational and experimental study, (56) we found that solution ions may affect the outcome of ASEC-FEG calculations, especially when there are charged residues inside the active site of a flavoprotein. Therefore, we repeated the calculations for both iLOV and iLOV-Q430E after adding 4 pairs of Na+ and Cl-solution ions, approximately 1 NaCl per 2775 water solvent molecules, equivalent to 20 mM of salt used in the experiments in this work.…”
Section: Resultsmentioning
confidence: 93%
“…(61) We recently developed ASEC-FEG for flavoproteins. (56,62) With ASEC, the quantum chemical calculations are performed in the field of a time-averaged electrostatic potential environment of the protein and solution (collectively referred to as a "solvent" in the ASEC acronym). Effectively, the protein and solution are represented as a "superposition" of structures obtained from MD simulations.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…An important next step would be to test the accuracy of continuum or explicit solvent models in predicting solvent effects on oscillator strengths . Both implicit and explicit models appear to successfully predict trends in oscillator strengths for the same molecule in different environments, , but it is not yet clear if such predictions are quantitative. Preparing a benchmark set of experimental oscillator strengths for gas-phase UV–visible spectra would also be informative, but is more challenging because gas-phase spectra tend to have well-resolved vibronic transitions that are more difficult to integrate.…”
Section: Discussionmentioning
confidence: 99%